Factors Affect to Relationship Marketing for Creating Customer Loyalty in Hospital Services Business - Afifi, Iqbal; Amini, Ahdia (ASEAN Marketing Journal, 2021)
Manuscript type: Research paper. Research Aims: The purpose of this paper is to understand and answer problems from the variables of service quality (interaction quality, physical environment quality, & outcome quality), customer trust, customer value, and customer loyalty to hospital consumer that has applied JCI standard accreditations through green hospital concept. Design/methodology/approach: The study uses a descriptive research design, with 209 valid respondents. SPSS is used to pretest the variables that well construct variables, and SEM to analyze significant construct variables and influence the construct variables. Research Findings: There study findings are: 1) interaction quality, physical environment quality, and outcome quality positively influences customer trust; 2) customer trust positively influences customer value; 3) customer value positively influences customer loyalty; 4) customer trust negatively influences customer loyalty; and 5) the mediating effect of customer value positively influences customer trust and customer loyalty in high to a great extent, so it can have a full mediating effect. Originality/value: The study is one of the few empirical investigations into service quality based on customer trust, customer value, and customer loyalty in the healthcare industry that implements the green hospital concept, builds long-term relationships between customers and medical staff, and the healthcare is doing the examining the mediating effects of customer value on customer trust and customer loyalty. Practitioner/Policy Implications: This study can explain customer trust, customer value, customer loyalty based on hospital services quality through relationship marketing. Hospital has been applied JCI standard accreditation through green hospital build long-term relationship for their customer and good businesses for its hospital. Research limitation/Implications: The research results indicate that service quality is the basic step in increasing customer trust, customer value and customer loyalty in hospital management. The findings of the study will help hospital management to 1) build relationships between medical staff and their customers, and create customer loyalty in long-term relationships, 2) to develop and implement the green hospital concept based on Joint Commission International standards within a green marketing framework.